2001
DOI: 10.1034/j.1600-0706.2001.930205.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transmission of Baylisascarisprocyonis to intermediate hosts as a function of spatial scale

Abstract: 2001. Changes in transmission of Baylisascaris procyonis to intermediate hosts as a function of spatial scale. -Oikos 93: 213-220.Physical changes in landscapes alter the abundance and distribution of species. Higher-order effects can occur when changes in ecological processes result in altered interspecific interactions and subsequent changes in a species' abundance or persistence. Baylisascaris procyonis, a roundworm parasite of raccoons (Procyon lotor), is pathogenic to numerous small vertebrates that serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 48 publications
1
41
1
Order By: Relevance
“…Probability of infection at individual sites ranged from 17% to 42%, and was 33% across all sites (Table 1). Overall, prevalence was slightly higher in our study than the 28% observed by Page et al (2001a) in a fragmented agricultural land- scape in Indiana and the 29% prevalence that Eagan (2009) found in a similar agricultural landscape. Prevalence was much higher than the 6% observed in a large, intact forest by Page et al (2001a).…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Probability of infection at individual sites ranged from 17% to 42%, and was 33% across all sites (Table 1). Overall, prevalence was slightly higher in our study than the 28% observed by Page et al (2001a) in a fragmented agricultural land- scape in Indiana and the 29% prevalence that Eagan (2009) found in a similar agricultural landscape. Prevalence was much higher than the 6% observed in a large, intact forest by Page et al (2001a).…”
contrasting
confidence: 51%
“…populations near Chicago, Illinois, USA. Mice are a common intermediate host of the parasite (Page et al, 2001b). Though both whitefooted (Peromyscus leucopus) and deer mice (Peromyscus maniculatus) likely occurred at our study sites, we combined the species for analysis because of the difficulty of making a definitive species identification for many individuals.…”
mentioning
confidence: 99%
“…Susceptibility varies across species lines, but most paratenic hosts are highly susceptible to B. procyonis infection and suffer clinical effects of NLM (1). In a survey in a fragmented agricultural landscape, Page et al (28) found a large proportion (28%) of white-footed mice (Peromyscus leucopus) to be infected with B. procyonis larvae, and this species appears to represent a common and well-adapted paratenic host. Experimentally, most P. leucopus mice became infected at a lower level and had a longer average onset of CNS disease than laboratory mice (Mus musculus), but the majority still developed clinical signs (19).…”
Section: Biology Life Cyclementioning
confidence: 99%
“…In 2012 for the very first time, a chapter in a conservation textbook was dedicated to links be tween habitat loss, habitat fragmentation and infectious disease ecology (Suzan et al 2012). Habitat loss and fragmentation can affect infection dy namics via a variety of mechanisms, including hindering animal movement, impeding gene flow (Coulon et al 2004), facilitating edge effects (Chapman et al 2006a), introducing environmental contamination (Deem et al 2001), altering the ecology of intermediate hosts (Page et al 2001), changing host population size and density (Mbora & McPeek 2009), limiting nutrition (Chapman et al 2006b), facilitating contact and conflict with people (Nelson et al 2003), and subjecting animals to psychological and physiological stress, thereby affecting immunocompetence (McCallum & Dobson 2002). Parasites have the potential to be used as indicators of stress in wildlife threatened by habitat fragmentation (Schwitzer et al 2010).…”
Section: Introductionmentioning
confidence: 99%